The Analysis of Juvenalian Satire in The Script Of Prabowo Vs Jokowi - Epic Rap Battles Of Precidency in Skinny Indonesian 24 Youtube Channel - Siti Rokhani; Waode Hamsia; Radius Setiyawan (Universitas Muhammadiyah Surabaya, 2022)
Abstract: Â This research analyzed the satirical political communication that was used by Skinny Indonesian 24 YouTube channel in the script of epic rap battles of presidency Prabowo and Jokowi remake.This research discussed about satirical political communication that gave some critical perception for the viewers especially for Indonesian citizen. The researcher focused on the statements and utterances that were used by Jokowi and Prabowo remake in the script of epic rap battles, theories by Mark Boukes (2018), MasterClass Staff (2021), Olivera Tesnohlidkova (2020), Melinda Alliker (2007), Edley Luke (2017), and Evan Gottlieb (2021) . The researcher used Qualitative research to find kind of satirical political communication used by Skinny Indonesian 24 Youtube channel and the reason why Skinny Indonesian 24 Youtube channel used satirical political communication. From this research the researcher found out kind of satire that was used by Skinny Indonesian 24 Youtube channel in the script of Epic rap battles of precidency Prabowo and Jokowi remake and the reason why it was used in that youtube channel. The researcher also found out that satirical political communication is the most suitable ways to attract more viewers in Youtube channel.Â Keyword: Satirical Political Communication; Satire; Epic Rap Battles of Precidency; Skinny Indonesian 24 Youtube channel